Dinamika Politik dan Perkembangan Islam di Kerajaan Selaparang, Nusa Tenggara Barat - arief rahman; Buana Setiono (Lembaga Publikasi Ilmiah Nusantara, 2026)
The Selaparang Kingdom was one of the important centers of power on Lombok Island and played a significant role in the development of Islam in the West Nusa Tenggara region. The political dynamics that occurred within this kingdom were not only related to struggles for power but also influenced the processes of the spread, acceptance, and strengthening of Islamic values in the life of the community. This community service activity aims to increase public understanding—especially among the younger generation and local community leaders—regarding the political history and the development of Islam in the Selaparang Kingdom as part of local cultural heritage and identity. The methods used in this activity include an educational-participatory approach through local history outreach, group discussions, and the utilization of historical sources such as literature, oral traditions, and cultural relics that are still found within the community. The results of the activity show an increase in public knowledge and awareness regarding the role of the Selaparang Kingdom in the Islamization process in Lombok, including the influence of political relations with other kingdoms, Islamic scholars (ulama), and trade networks that accelerated the spread of Islam. In addition, this activity also encourages the community to become more active in preserving and maintaining historical values and local wisdom related to the development of Islam in the region. Thus, strengthening local historical literacy through community service activities can become an important means of building cultural identity, reinforcing Islamic values, and fostering a sense of ownership toward the region’s historical heritage.